BRIGHENTI, Clovis Antonio. Estrangeiros na própria terra: Presença Guarani e Estados Nacionais, Florianópolis/Chapecó: Ed. UFSC/Argos, 2010, 282 pp. - Mainardi, Camila (Revista de Antropologia, 2013)
BRIGHENTI, Clovis Antonio. Estrangeiros na própria terra: Presença Guarani e Estados Nacionais, Florianópolis/Chapecó: Ed. UFSC/Argos, 2010, 282 pp.